An analysis of higher order thinking skills on three English textbooks for senior high school - Sainyakit, Paulus; Yulia, Yuyun (Universitas Sarjanawiyata Tamansiswa, 2021)
Abstract: This research aims at finding the empirical evidence of the higher order thinking skill distribution based on revised edition of Bloom’s taxonomy in three English textbooks, namely: Pathway to English, Bahasa Inggris, and Buku Teks Pendamping Bahasa Inggris untuk SMA/MA/SMK/MAK revised edition for the eleventh-graders of senior high school students and investigating the difference among those three English textbooks related to the higher order thinking skills (HOTS). This research used content analysis method. In collecting data, this research used checklist table to collect qualitative data in form of words which were on essay questions. It employed analysis card as the instrument to analyze the data. The results found that each textbook had different distribution of the HOTS that consisted of three skills, namely: analyzing skills or C4, evaluating skills or C5, and creating skills or C6. The analyzed skill in Pathway to English textbook and Bahasa Inggris (Buku Teks Pendamping) obtained same portion of distribution which contained 23 questions while Bahasa Inggris textbook only obtained 2 questions. Further, evaluating skills in Bahasa Inggris textbook obtained the highest distribution among others with 34 questions, Pathway to English textbook as the second obtained 22 questions while Bahasa Inggris (Buku Teks Pendamping) obtained 11 questions. Finally, creating skills from the English textbooks obtained the lowest distribution. Pathway to English textbook obtained 5 questions, Bahasa Inggris textbook obtained 6 questions and Bahasa Inggris (Buku Teks Pendamping) obtained 1 question. This research concludes that the skills of the HOTS among three English textbooks that analyzed skill or C4, evaluated skill or C5, and created skill or C6 were conditionally different and unequal to each other related to the distribution. Keywords: English textbooks, essay reading exercise, higher order thinking skill.